1999
DOI: 10.7863/jum.1999.18.10.691
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrasonographic technology to assess and compare echodensity of fetal bowel, bone, and liver in the second trimester of pregnancy.

Abstract: Increased fetal bowel echogenicity in the second trimester is used as a marker for prenatal diagnosis of Down syndrome. The diagnosis of hyperechogenicity is subjective. We sought to quantify and correlate fetal bowel echogenicity with liver and bone in 47 normal fetuses, using three‐dimensional ultrasonographic technique and objective measurement of gray scale distribution. No significant change was found in the organs' echogenicity between 15 and 24 weeks of gestation, the optimal time for detection of fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, 13% of participants also stated they made comparisons to other fetal structures, such as liver and lung, concurring with previous studies. [11][12][13][14] These participants did not offer any additional detail on how this occurred in practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, 13% of participants also stated they made comparisons to other fetal structures, such as liver and lung, concurring with previous studies. [11][12][13][14] These participants did not offer any additional detail on how this occurred in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The subjective assessment does not appear to depend on sonographer experience 12 . Khandelwal et al 13 attempted to objectively measure the echogenicity of the fetal bowel, comparing it to the echogenicity of the liver and bone using a grayscale distribution (0–255), and found that the echogenicity of the liver, bone, and bowel was constant during weeks 15 to 24 of gestation, and it varied widely after 26 weeks. Despite this objective measurement, the normal range was still wide, making the diagnosis of fetal bowel echogenicity difficult.…”
Section: Discussionmentioning
confidence: 99%